Comparison between Cementless and Cemented Bipolar Hemiarthroplasty for Treatment of Unstable Intertrochanteric Fractures: Systematic Review and Meta-analysis - Yoo, Jun-Il (Hip Pelvis, 2018)
PURPOSE: This study was conducted to compare cemented and cementless bipolar hemiarthroplasty in elderly patients with unstable intertrochanteric fractures via meta-analysis and systematic review of relevant studies. MATERIALS AND METHODS: Systematic review and meta-analysis were performed on 31 available clinical studies; 19 of these studies used cemented stems, 12 used cementless stems, one used both types of stems, and two studies involved a comparative analysis of both stem types. RESULTS: There were statistically significant differences in rates of leg length discrepancy (LLD) greater than 1 cm between the cemented (event rate, 0.089) and cementless groups (event rate, 0.015 and 0.047; P=0.03). CONCLUSION: Cemented bipolar hemiarthroplasty and cementless bipolar hemiarthroplasty performed on elderly patients with unstable intertrochanteric fracture revealed similar mortality and complication rates; however, the rate of LLD greater than 1 cm was significantly higher in the cemented group compared with the cementless group.